Targeted macrophage mannose receptor (CD206)-specific protein delivery via engineered extracellular vesicles - Leyla A. Ovchinnikova; Daria Y. Tanygina; Samir S. Dzhelad; Evgeniy G. Evtushenko; Dmitriy V. Bagrov; Alexander G. Gabibov; Yakov A. Lomakin (Heliyon)
Extracellular vesicles (EVs) show great potential for therapeutic delivery to human cells, with a focus on modulating immune responses. The most promising targets for inducing humoral and cellular immunity against a specific antigen are macrophages (Mϕs) and dendritic cells (DCs). Targeting mannose receptors (CD206), which are highly expressed on these antigen-presenting cells, to promote the presentation of specific antigens through EV-mediated uptake, is a promising strategy in clinical immunotherapy. Our study compares two EV-fused anti-CD206 nanobodies in delivering cargo proteins to human activated antigen-presenting cells. We demonstrated that nanobody-functionalized EVs exhibit enhanced interaction and increased uptake by CD206+ cells compared to non-targeted EVs. Furthermore, replacing the full-length vesicular stomatitis virus protein G (VSV-G) with its truncated form, fused to a monoclonal anti-CD206 nanobody, significantly improves the specificity of EV uptake by CD206+ cells. Our study outlines an optimized platform for the production of targeted EVs designed for specific protein delivery to CD206-positive human cells.